Gray Matter Deterioration Pattern During Alzheimer's Disease Progression: A Regions-of-Interest Based Surface Morphometry Study - Wu, Zhanxiong; Peng, Yun; Hong, Ming; Zhang, Yingchun (Frontiers in Aging Neuroscience, 2021)
Accurate detection of Alzheimer's Disease (AD) lesion regions is critical for early intervention to effectively slow down the progression of the disease. Although gray matter volumetric abnormalities are commonly detected in patients with mild cognition impairment (MCI) and AD, gray matter surface-based deterioration pattern associated with the progression of the disease from MCI to AD stages is largely unknown. To identify group differences in gray matter surface morphometry including the cortical thickness, gyrification index, and sulcus depth, 80 subjects from the ADNI database were split into healthy controls (N=20), early MCIs (EMCI) (N=20), late MCIs (LMCI) (N=20), and ADs (N=20). Regions-of-interest (ROI)-based surface morphometry was subsequently studied and compared across the 4 stage groups to characterize the gray matter deterioration over AD progression. Co-alteration patterns (Spearman correlation coefficient) across the whole brain were also examined. Results showed that patients with MCI and AD exhibited a significant cortical thickness reduction (p<0.001) mainly in cingulate region (4 subregions), temporal (13 subregions), parietal (5 subregions), and frontal (6 subregions) lobes compared to healthy controls. The sulcus depth of the 8 temporal, 4 frontal, 4 occipital, and 8 parietal subregions were also significantly affected (p<0.001) by AD progression. The Gyrification index was shown to be insensitive to AD progression (only three subregions were detected with significant difference, p<0.001). Moreover, Spearman correlation analysis confirmed that the co-alteration pattern of the cortical thickness and sulcus depth indices is predominant during AD progression. The findings highlight the relevance between gray matter surface morphometry and AD stages, laying the foundation for in vivo tracking of AD progression. The co-alteration pattern of surface-based morphometry may improve our knowledge of the underlying pathologic mechanisms in AD.